An Investigation of the Educational Problems of Gifted Children in the Preschool Period According to the Perspectives of Mothers - Fatma Betül Şenol (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: When the development of gifted children is noticed and supported by their teachers in the preschool period, the problems they experience in education life become minimized. The aim of the study is to determine the problems experienced by gifted children in the preschool period. For this purpose, the effects of informing mothers about the development of their gifted children in the preschool period, the educational problems experienced by the children in preschool education institutions, and the expectations of mothers from preschool education were examined in line with the perceptions of the mothers.Method: The study was planned in a phenomenological pattern, one of the qualitative research methods. The study group consists of 75 mothers with gifted children determined through the criterion sampling method. Data were collected through semi-structured interviews and were analyzed with the content analysis technique.Findings: In the study, it was determined that preschool teachers gave information to families about their children's different developmental characteristics, learning skills, giftedness, and creativity. The educational problems experienced by gifted children in the preschool period were grouped under the themes of the activity applied, the materials used, the teacher, peer interaction, and the school. The expectations of mothers from preschool education were gathered under the themes of activity, teacher, educational environment, social emotional development, and early identification.Discussion: Since most of the gifted children were noticed in the preschool period by their teachers who did not make adequate interventions, educational problems arose. The expectation of families from preschool education is that their educational problems are solved.Conclusion: Recognition of gifted children in the preschool period is the beginning of their education process that will improve their potential. Therefore, educational measures should be taken to maximize the potential of these children and to minimize the problems they experience.